1991
DOI: 10.1104/pp.95.2.450
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Antifungal Chitinase from Arabidopsis thaliana

Abstract: Plants exhibit an altered pattern of protein synthesis in response to pathogen invasion and abiotic stress. One of these ;pathogenesis-related' proteins has been identified as chitinase, which is capable of inhibiting fungal growth in vitro. This observation has led to the suggestion that the in vivo role of chitinases is to protect plants against fungal invasion. Here, we report the purification and characterization of a basic chitinase from Arabidopsis thaliana (L.) Heynh. Columbia wild type. The purified en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 25 publications
2
55
0
1
Order By: Relevance
“…However, since chitin is a major component of the cell walls of many fungi (Bartnicki-Garcia, 1968), it has been hypothesized that this enzyme may be involved in plant defense reactions. In support of this hypothesis, it has been shown that the purified enzyme restricts fungal growth in vitro (Broekaert et al, 1988;Mauch et al, 1988;Verberg and Huynh, 1991), although several of the isolated chitinases do not possess antifungal activity (Woloshuk et al, 1991;SelaBuurlage et al, 1993), and in some cases transgenic plants transformed with chitinase genes did not show increased resistance against pathogens (Neuhaus et al, 1991;Nielsen et al, 1993). These observations and the facts that some chitinase genes are expressed in the absence of pathogens and that their expression may be controlled in an organspecific and developmental manner (Kombrink et al, 1993) raise the question of their possible participation in other cellular processes.…”
Section: Discussionmentioning
confidence: 91%
“…However, since chitin is a major component of the cell walls of many fungi (Bartnicki-Garcia, 1968), it has been hypothesized that this enzyme may be involved in plant defense reactions. In support of this hypothesis, it has been shown that the purified enzyme restricts fungal growth in vitro (Broekaert et al, 1988;Mauch et al, 1988;Verberg and Huynh, 1991), although several of the isolated chitinases do not possess antifungal activity (Woloshuk et al, 1991;SelaBuurlage et al, 1993), and in some cases transgenic plants transformed with chitinase genes did not show increased resistance against pathogens (Neuhaus et al, 1991;Nielsen et al, 1993). These observations and the facts that some chitinase genes are expressed in the absence of pathogens and that their expression may be controlled in an organspecific and developmental manner (Kombrink et al, 1993) raise the question of their possible participation in other cellular processes.…”
Section: Discussionmentioning
confidence: 91%
“…In all cases studied so far, infection of plants by pathogenic microorganisms caused massive coordinated accumulation of several chitinase and 1,3$-glucanase isoenzymes. In bean, pea, potato and arabidopsis, several chitinases have been found to possess lysozyme activity (Boller et al, 1983;Mauch et al, 1988a;Verburg and Huynh, 1991;Witte, 1991). In the rubber tree, one acidic chitinase showed no lysozyme activity, whereas six basic isoforms from the same plant exhibited lysozyme activity to varying degrees (Martin, 1991).…”
Section: Purification and Characterization Of Extracellular Acidic Cmentioning
confidence: 99%
“…A significant over-representation of genes associated with systemic acquired resistance and the SA-mediated signalling pathway was observed in the upregulated genes in the TobEA dataset, including presumptive orthologues of ENHANCED SUSCEPTIBILITY 1 (EDS1) and PHYTOALEXIN DEFICIENT 4 (PAD4), central regulators of SA-mediated defence (Figures 1H and I There was also significant over-representation of Gene Ontology categories associated with defence against fungal pathogens as well as cell death and innate immune responses in leaves at more advanced stages of senescence. These included a homologue of the Arabidopsis basic chitinase PR3 (Verburg and Huynh 1991) in addition to other components of plant immunity/defence. This supports the growing evidence that pathogen defence and senescence share common components (Quirino et al, 1999;Feys et al, 2005), presumably largely via the use of similar signalling pathways leading to accumulation of reactive oxygen species and cell death (Yoshida, 2003).…”
Section: Gene Expression Changes In Senescing Tobacco Leavesmentioning
confidence: 99%